Graphing of Functions and Graphical Aspects in Lessons of Secondary School Mathematics Textbooks in Nepal: A Problem Analysis Approach - Pathak, Santosh; Poudel, Eeshwar (Academic Journal of Mathematics Education, 2024)
To assess students' achievement in graphing functions and understanding various mathematical concepts, we analyzed exercises from secondary-level mathematics textbooks (grades 9-12) in Nepal. The focus was on the concept of functions, their graphs, applications, and related problems. Each problem was categorized based on its context, expected response, and cognitive demand using a mixed-methods approach. The findings reveal a significant lack of emphasis on problem types crucial for developing graphing skills and applying functions in problem-solving contexts. Instead, there is an overabundance of certain problem types, underscoring the need for a more balanced distribution of exercises across different learning dimensions. This paper discusses the implications of these findings for curriculum developers and textbook authors.